The school of exegesis and free scientific inquiry: Legal Hermeneutics Reflexes in Brazil (1873 to 1887) - Cavalcante , Jéssica Painkow Rosa; Batista , Leonardo Matheus Barnabé; Macêdo , Maurides (Seven Editora, 2023)
The objective of this article, through a literature review, is to present an overview of the School of Exegesis, the Scientific School and the Free Law Movement. Through the study of classical authors who wrote on the themes, it seeks to relate the main characteristics of the School of Exegesis, of Free Scientific Inquiry, and to show the development of the Free Law Movement in Germany. From this study it is intended to discuss how the debate about legal hermeneutics in Brazil in the nineteenth centu-ry took place, analyzing the influences suffered in the heyday of the School of Exe-gesis (1830-1880). The research methodology was bibliographic research and analy-sis of documentary sources. For the analysis of legal hermeneutics in Brazil, the Le-gal Journals of circulation of the time were used as a source. DOI:https://doi.org/10.56238/interdiinovationscrese-007